1976
DOI: 10.1143/jjap.15.1485
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Intermediate States on Multiphoton Ionization of Hg Atoms by Laser Radiation

Abstract: The multiphoton ionization of the Hg atom by the intense radiation of a ruby laser is studied over the wide range of pressures from 1 to 1600 Torr, comparing with the experiments on iodine vapour. The six photon process occurs at 1 Torr. The three photon process is experimentally found at the pressure of 200 Torr and over. The five photon process is shown to exist at pressures of 50 and 100 Torr. It is considered that metastable states of the Hg atom affect multiphoton ionization. In addition, the abrupt incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

1981
1981
1991
1991

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…Support for this possible mechanism also comes from the argument that only a small fraction of the 0.05-nm bandwidth contributes to the pumping of the two-photon transition while all of the available laser energy contributes to the nonresonant transition into ionization. The saturation of absorption of the last photon from a bound state into ionization has also been reported elsewhere (8) where different energy levels and wavelengths were involved. However, other possible absorption mechanisms that involve partial saturation of one or both of the above steps cannot be ruled out.…”
Section: Methodssupporting
confidence: 57%
See 1 more Smart Citation
“…Support for this possible mechanism also comes from the argument that only a small fraction of the 0.05-nm bandwidth contributes to the pumping of the two-photon transition while all of the available laser energy contributes to the nonresonant transition into ionization. The saturation of absorption of the last photon from a bound state into ionization has also been reported elsewhere (8) where different energy levels and wavelengths were involved. However, other possible absorption mechanisms that involve partial saturation of one or both of the above steps cannot be ruled out.…”
Section: Methodssupporting
confidence: 57%
“…Hg vapor has been previously analyzed by the multiphoton ionization technique in both a nonresonant (7) and resonant (8,9) manner. However, in these papers the laser wavelengths were quite different (longer) than in this study, no analytical detection limits were reported nor were there any Hg radiation analyses presented.…”
Section: Correspondence Multiphoton Ionization and Emission Analysis ...mentioning
confidence: 99%
“…Samples of solid particles weighing up to 1 mg, suspended in 2propanol, can be analyzed with good accuracy and minimal concomitant effects (2). Difficulties arise, however, in the analysis of aqueous solution residues weighing much more than 500 ng, probably because they are in the form of localized thick salt crusts that are difficult to vaporize completely (2,3). The formation of thick crusts prohibits direct determination of trace metals in saline solutions without a separation step (3).…”
Section: Resultsmentioning
confidence: 99%
“…Support gases were dry air at 700 torr and a flowing mixture of 40:60 02-Ar at atmospheric pressure. The discharge chamber and discharge characteristics have been described (1,2,4). Thin Film Production.…”
mentioning
confidence: 99%